Ash production by attrition in volcanic conduits and plumes - T. J. Jones; J. K. Russell (Scientific Reports, 2017)
Abstract Tephra deposits result from explosive volcanic eruption and serve as indirect probes into fragmentation processes operating in subsurface volcanic conduits. Primary magmatic fragmentation creates a population of pyroclasts through volatile-driven decompression during conduit ascent. In this study, we explore the role that secondary fragmentation, specifically attrition, has in transforming primary pyroclasts upon transport in volcanic conduits and plumes. We utilize total grain size distributions from a suite of natural and experimentally produced tephra to show that attrition is likely to occur in all explosive volcanic eruptions. Our experimental results indicate that fine ash production and surface area generation is fast (<15 min) thereby rapidly raising the fractal dimension of tephra deposits. Furthermore, a new metric, the Entropy of Information, is introduced to quantify the degree of attrition (secondary fragmentation) from grain size data. Attrition elevates fine ash production which, in turn, has consequences for eruption column stability, tephra dispersal, aggregation, volcanic lightening generation, and has concomitant effects on aviation safety and Earth’s climate.